Phylogeographic mitogenomics of Atlantic cod Gadus morhua: Variation in and among trans‐Atlantic, trans‐Laurentian, Northern cod, and landlocked fjord populations. Issue 13 (1st June 2018) - Lait, Linda A.; Marshall, H. Dawn; Carr, Steven M.
Abstract: The historical phylogeography, biogeography, and ecology of Atlantic cod ( Gadus morhua ) have been impacted by cyclic Pleistocene glaciations, where drops in sea temperatures led to sequestering of water in ice sheets, emergence of continental shelves, and changes to ocean currents. High‐resolution, whole‐genome mitogenomic phylogeography can help to elucidate this history. We identified eight major haplogroups among 153 fish from 14 populations by Bayesian, parsimony, and distance methods, including one that extends the species coalescent back to ca. 330 kya. Fish from the Barents and Baltic Seas tend to occur in basal haplogroups versus more recent distribution of fish in the Northwest Atlantic. There was significant differentiation in the majority of trans‐Atlantic comparisons (ΦST  = .029–.180), but little or none in pairwise comparisons within the Northwest Atlantic of individual populations (ΦST  = .000–.060) or defined management stocks (ΦST  = .000–.023). Monte Carlo randomization tests of population phylogeography showed significantly nonrandom trans‐Atlantic phylogeography versus absence of such structure within various partitions of trans‐Laurentian, Northern cod (NAFO 2J3KL) and other management stocks, and Flemish Cap populations. A landlocked meromictic fjord on Baffin Island comprised multiple identical or near‐identical mitogenomes in two major polyphyletic clades, and was significantly differentiated from all other populations (ΦST  = .153–.340). The phylogeography supports a hypothesis of an eastern origin of genetic diversity ca. 200–250 kya, rapid expansion of a western superhaplogroup comprising four haplogroups ca. 150 kya, and recent postglacial founder populations. Abstract : The study provides a new perspective on Atlantic cod phylogeography through the use of mitogenomic analysis. We challenge the previous suggestion of a Northwest Atlantic "codmother" and instead identify a European origin to the current distribution and diversity in Atlantic cod. A unique pattern of variation is uncovered in one of the three Canadian Arctic fjords, trans‐Atlantic differences are highlighted, and a lack of phylogeographic structure in the Northwest Atlantic cod stocks is confirmed.